If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + -2 = 2k + 4 Reorder the terms: -2 + 4k = 2k + 4 Reorder the terms: -2 + 4k = 4 + 2k Solving -2 + 4k = 4 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. -2 + 4k + -2k = 4 + 2k + -2k Combine like terms: 4k + -2k = 2k -2 + 2k = 4 + 2k + -2k Combine like terms: 2k + -2k = 0 -2 + 2k = 4 + 0 -2 + 2k = 4 Add '2' to each side of the equation. -2 + 2 + 2k = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 2k = 4 + 2 2k = 4 + 2 Combine like terms: 4 + 2 = 6 2k = 6 Divide each side by '2'. k = 3 Simplifying k = 3
| 240.00+x(0.25)=405.00 | | 2(0.3x+4)-1=1.33x-3+x | | 25+(5x)=50+(10x) | | 10pq+8p= | | -3h-4=h-8 | | 4=(m+13) | | 81-x=93-2x | | 5+-11t=7(5+-2t) | | 8x^2+7x-4=0 | | 7g(-3h+1)= | | 81-x=93-x | | 2a+2=a+4 | | 79-(101-5y)=2(101-5y)+y | | 6.5(x-4)=-0.5x+30 | | 5=(x+8) | | -5x+6y=30 | | 19x=12x | | 11x+2=5x+10+58 | | -5-x=1+2x | | 4d=7-7 | | 8x+2+70+60= | | -5(a-6)+2a=9 | | (3x-6y-1)+(-x+y+10)= | | 3w+10=-3+8w-9w | | 4(2y+1)-2y=-26 | | 1/3(102-12c)=5(3c+10) | | 5x-x-3=2x+6 | | M-3=7m-21 | | 4n-(7-6n)=13 | | 6x+3=3(2x+3) | | 2x-11=23 | | 3x=52 |